Collaborative Governance in a Developing Non-Democracy: Uganda's Organizational Success Fighting HIV/AIDS. Issue 3 (April 2022) - Ryan, Michael P.
Organization and management scholars seek theory-grounded and theory-building research regarding establishing and structuring organization forms to tackle large, intractable problems, especially grand challenges of poverty, disease, and hunger. Developing countries tend to have intractable social problems of rampant poverty and poor health and struggle with epidemics. The case of HIV/AIDS in Uganda contributes new understanding regarding public organization and state capacity in developing countries, especially regarding grand challenges of intractable social problems. Field research study of HIV/AIDS action in Uganda contributes unexpected insights regarding collaborative governance in an institution context under-explored in public administration and organization studies, the developing non-democracy . Ugandan public executives innovated a participatory organization model of cross-sector collaborative governance to fight their intractable social problem of HIV/AIDS during their start-up era. The participatory organization model innovated by the Ugandan public chief executive, called a best practice by WHO/UNAIDS and influential with PEPFAR designers, yields a construct of network coordination and network control for study of the organization of cross-sector collaborative governance. Integration of public administration and organization studies with development and international relations studies informs study of tensions between efficiency and inclusiveness and between social power and social legitimacy with respect to collaborative governance outcomes of network effectiveness and participatory accountability in the institution context of a developing non-democracy. Is non-democracy meaningful or meaningless to collaborative governance?